High‐pressure study of the thermoelectric properties of various oxides (ZnO, Ti2O3, FexOy) and FeAs‐based compounds. Issue 4 (2nd April 2013) - Morozova, Natalia V.; Khmeleva, Iuliia A.; Ovsyannikov, Sergey V.; Karkin, Alexander E.; Shchennikov, Vladimir V.
Abstract: In the present work the results of investigation of the thermoelectric (TE) properties of some Zn, Ti and Fe oxides and FeAs‐based compounds under compression up to 20 GPa are reported. The data obtained of thermoelectric power S dependence on pressure P for the materials under consideration revealed some new features of the electron properties of both initial and high‐pressure phases (RS‐ZnO). For FeAs‐based compounds the complex behavior of S on P was found depending probably on the contribution of d‐states in the conductivity. The decreasing of the semiconductors gap has been established under pressure for the narrow‐gap semiconductors Ti2 O3 and Fe2 O3 ; the sign inversion being observed in the first oxide pointing to the change of dominant type of the charge carries. Pressure cycling of Fe2 O3 led to a nanostructured state with the modified electronic properties. TE data at high pressure allowed the electronic properties of the materials with the different type of the electron structure to be detailed.